Cardiovascular changes occurring with occlusion of a mature arteriovenous fistula. Issue 6 (November 2015) - Aitken, Emma; Kerr, Daniele; Geddes, Colin; Berry, Colin; Kingsmore, David
Background: The aim of this study was to evaluate the relationship between Qa, cardiovascular parameters and symptomatic cardiac disease. Methods: A prospective cohort study of 100 patients dialysing via an arteriovenous fistula (AVF) was performed. Qa was measured using pulsed Doppler ultrasound. Cardiovascular parameters were measured using thoracic bioimpedance technique (Medis, GmbH). Measurement of cardiovascular parameters was undertaken pre- and post-occlusion of the AVF. Results: Mean age was 57.1 years (range: 19-83); 51% male. Mean values pre-occlusion: mean arterial blood pressure (MABP) 89.6 ± 16.9 mmHg; stroke volume index (SVI) 39.3 ± 4.6 mL; cardiac index (CI) 3.7 ± 0.8 L/min/m 2 ; systemic vascular resistance index (SVRI) 585.5 ± 67.8 dyn/sec/cm −5 /m 2 ; oxygen delivery (DO2 I) 607.1 ± 116.8 mL/min/m 2 . A total of 12% of patients had CI>4.5 L/min/m 2 pre-occlusion. There was no difference in heart rate (HR), MABP and SVI following occlusion of AVF. Mean CI reduced post-AVF occlusion (∆CI: -0.42 L/min/m 2 ; p<0.001), as did DO2 I (∆ DO2 I: 45.5 mL/min/m 2 ; p<0.001). SVRI increased (∆SVRI: 170.1 dyn/sec/cm −5 /m 2 ; p<0.001). The drop in CI which occurred post-AVF occlusion was greater in patients with Qa >2000 mL/min (-2.79 ± 0.34 vs. -0.24 ± 0.48 L/min/m 2 ; p<0.001). There was a non-significant trend towards symptomatic heart failure in those patients with a greater ∆CI following AVF occlusion (NYHA 1: -0.1 ± 0.1 L/min/m 2 ; NHYA 2: -0.3 ± 0.7 L/min/m 2 ; NYHA 3: -0.7 ± 1.0 L/min/m 2 ; p = 0.06). Conclusions: The relationship between AVF blood flow, cardiac output and symptomatic cardiac disease is complex. Occlusion of an AVF leads to reduced cardiac output and improved oxygen delivery, even in asymptomatic patients. This difference is most marked in patients with high-flow AVF (>2000 mL/min). High-flow AVF with large ∆CI may lead to high cardiac output state, which is reversible on occlusion of the AVF.